Principals' instructional leadership practices in Pakistan elementary schools: perceptions and implications - Khan, Adeel Ahmed; Asimiran, Soaib; Abdul Kadir, Suhaida; Basri, Ramli (Horizon Research Publishing, 2020)
Purpose: The purpose of this article is to outline the findings of an empirical study, ‘Principals' instructional leadership practices in Pakistan Elementary schools'. This study aims to explore the instructional leadership practices in elementary schools in Pakistan. This study also intends to examine the conceptualization of instructional leadership within the context of Pakistan. This study categorizes the confines of the existing knowledge established on instructional leadership practices and also for enlightening a preliminary empirical understanding of how principals perceive and ratify their role as instructional leaders in Pakistan. Qualitative research design was used and semi-structured interviews were conducted with 42 elementary school principals in Pakistan. The sample included principals from 14 Government Rural Schools, 14 Government Schools in towns and 14 Government Schools in Urban areas. Initially qualitative data was analyzed inductively and successively coded to generate the findings and conclusions. Outcomes of the study indicated that Pakistani principals overall understood and defined tasks concerning to cultivate instructional practice. Specifically regarding supervision of teachers, how they monitored and evaluated the excellence of teaching and knowledge in their institutions. Data uncovered that more or less obligations and accomplishments related with being principal in Pakistan are mostly compatible with instructional leadership practices even without having the knowledge and recognition of the name of instructional leadership. Above all, monitoring and supervision of teaching and learning combined with leading professional learning were intensely signified in data. There is strong policy desire, delineated in the Pakistan National Education Policy that principals are responsible and answerable for overall improvement in the schools and supposed to be instructional leaders. Evidence indicates principals are ratifying some of the functions related to being an instructional leader but not others. The findings of this study offer some understandings into principals' instructional leadership practices in Pakistan. It also offers a base for morein-depth investigations that can further increase the knowledge regarding principals' instructional leadership practices in Pakistan.